2018
DOI: 10.11648/j.ijcda.20180401.13
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of Human Adult Occipital Condyle, Hypoglossal Canal and Foramen Magnum in Dry Skull of Modern Egyptians

Abstract: The present study investigated analyze some morphometric data about occipital condyles (OCs), hypoglossal canals (HCs) and foramen magnum (FM) for safety transcondylar surgical approach, and to compare the Egyptian skull measurements with that of the other races. A total of 75 dry skulls of unknown sex which were randomly chosen from the archives were used with exclusion of the extremely deformed or damaged. The parameters were measured by digital Vernier calipers with 0.01 mm precision and a protractor. Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
(51 reference statements)
1
0
0
Order By: Relevance
“…The present study is correlated with the study done by Swapnali Shamkuwar et al [11] 18.44mm and 38.59mm respectively. This study is in accordance with the findings of Vishal RJ et al [22] who reported the AICD as 18.23mm in males and 19.11mm in females.This study is also similar with the findings of Shimaa et al [23] who reported the anterior and PICDs as 18.97mm and 38.39mm respectively. These measured distances are lower than the results obtained by Kizilkant [24], Naderi.…”
Section: Discussionsupporting
confidence: 93%
“…The present study is correlated with the study done by Swapnali Shamkuwar et al [11] 18.44mm and 38.59mm respectively. This study is in accordance with the findings of Vishal RJ et al [22] who reported the AICD as 18.23mm in males and 19.11mm in females.This study is also similar with the findings of Shimaa et al [23] who reported the anterior and PICDs as 18.97mm and 38.39mm respectively. These measured distances are lower than the results obtained by Kizilkant [24], Naderi.…”
Section: Discussionsupporting
confidence: 93%
“…While in the Indian population, the mean length and width were recorded to be 23.60mm and 14.70mm, respectively [9]. Hence, these studies denote that population-specific differences regarding the morphology and morphometry of the occipital condyle exist [6].…”
Section: Introductionmentioning
confidence: 68%
“…If the Index is greater or equal to 1.2, then the morphology of the foramen magnum is said to be oval. However, if it is less or equal to 1.2, then the foramen magnum has an asymmetrical shape [6].…”
Section: Morphologymentioning
confidence: 99%
See 2 more Smart Citations